Стильові риси архітектури провінційного католицького барокового храму (на прикладі костьолів Київщини і Волині) - Горбик, Олена Олександрівна (КНУБА, 2003)
Дисертація на здобуття наукового ступеня кандидата архітектури за спеціальністю 18.00.01 -– теорія архітектури, реставрація пам’яток архітектури. – Київський національний університет будівництва та архітектури. –Київ, 2003. У дисертації розглянуто формування католицького провінційного барокового храму, визначено, що на теренах європейської католицької ойкумени в к.ХVІ-ХVІІІ ст. його становлення відбувалось залежно від діоцезально-регіональних та орденських пан-європейських традицій. На Україні присутніми були два варіанти бароко: колоніального католицько-європейського та національного українського православного, що мали відмінну періодизацію та незалежні напрямки розвитку. На Київщині і Волині формування католицького барокового храму являє синтез неоготичних та по-ренесансних барокових тенденцій. Провідником перших виступали ордени старої формації та біле духовенство, провідником других – новоорденські формації, єзуїти. Як перші, так і другі виробили специфічні стильові храмові структури, розвиток яких простежується за періодами. A candidate of architecture dissertation in Spieciality 18.00.01 – Theory of Architecture, Restoration of Architectural legency. Kyiv National University of Civil Engineering and Architecture. Kyiv. 2003. The forming of catholic baroque temple at Lutsk-Zhitomirskie episcopacy was considered at the dissertation. Determined, that the standard of temple-building among catholic eicumenie in XVI –XVIII centures took place in depends on episcopacy-regional and order’s main-European traditions. The style patterns of Roman baroque were interpreted in temple-building of the new-order’s formation , that expressed conflict between medieval and modern tendencies in counter-reformation outlook. This phenomenjn touched Ukraine as well because in the ХVІІ th-ХVІІ th centuries the Catholic culture had the possibility to affirmed on the territories which formed the Cahtolic Kingdom of Poland for the first time. This time is characterized by unprecedent activity of Catholic church-building in Ukraine: in the regions of Kyiv and Volhynia 65% of churches from the common number of Catholic churches of the ХІІ-ХХth centuries refer to the period of baroque. This is about 200 churches, 35% of them are retained. There were two baroque variants in Ukraine like colonial Catholic-European and national Ukrainian-Orthodox which had different division into periods and independent ways of development The forming of Catholic baroque temple in Kyiv and Volhynia regions is a synthesis of Neogothic and post-Renaissance baroque tendencies. The Neogothic baroque tendencies were used by the orders of old formation and post-Renaissance baroque tendencies – by new order formations (jesuits). Both established specific temple style models and we can retrace its development by periods.
Stylistic features of architecture of the provincial Catholic baroque temple (on an example of Roman-Catholic churches in Kyiv and Volhynia regions)
Keywords: літургійний контекст архітектури; традиції європейського храмобудування; орденські традиції; римська школа; Київська діоцезія; Луцько-Житомирська діоцезія; католицтво на Україні; діоцезальне храмобудування; староорденський; новоорденський тип храму; православне українське бароко; колоніальне провінційне католицьке європейське бароко; catholic baroque; liturgical context of architecture; traditions of the European temple-building; order’s traditions; Roman school; Kyiv’s episcopacy; Lutsk-Zhitomirskie episcopacy; Catholicism in Ukraine; episcopacy temple-building; old-order’s (‘’Dominican”) type of the temple, new-order’s (‘’Jesuits”) type of the temple; colonial Catholic baroque in Ukraine; Ukrainian-Orthodox baroque